2014
DOI: 10.1371/journal.pone.0110887
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Evidence for Domain-General Inhibitory Control during Bilingual Language Switching

Abstract: This paper presents an experiment that explored the role of domain–general inhibitory control on language switching. Reaction times (RTs) and event–related brain potentials (ERPs) were recorded when low–proficient bilinguals with high and low inhibitory control (IC) switched between overt picture naming in both their L1 and L2. Results showed that the language switch costs of bilinguals with high–IC were symmetrical, while that of bilinguals with low–IC were not. The N2 component failed to show a significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 29 publications
8
72
1
3
Order By: Relevance
“…The apparent similarity indirectly suggests that domain-general mechanisms support bilingual language switching (cf. Liu, Rossi, Zhou, & Chen, 2014).…”
Section: Switching Languages Versus Switching Listenersmentioning
confidence: 99%
“…The apparent similarity indirectly suggests that domain-general mechanisms support bilingual language switching (cf. Liu, Rossi, Zhou, & Chen, 2014).…”
Section: Switching Languages Versus Switching Listenersmentioning
confidence: 99%
“…For example, Linck et al (2012) and Liu, Rossi, Zhou, and Chen (2014) have shown that asymmetrical switch costs are, at least partially, related to inhibition, as measured by the Simon task (Simon, 1969). Yet, there are also arguments against using asymmetrical switch costs as a marker for inhibition.…”
Section: Asymmetrical Switch Costs As a Marker For Inhibitionmentioning
confidence: 99%
“…Note that the N2 component has also been investigated in other linguistic domains: comparing bilinguals with monolinguals (Fernandez et al, 2013), and in bilingual tasks where subjects switch between L1 and L2 while naming objects (Liu et al, 2014;Verhoef et al, 2009). Generally, studies using linguistic picture naming tasks elicited an N2 in a later time window (around 300-360 ms) than studies using more standard tasks such as tone detection (240-300 ms).…”
Section: The Present Studymentioning
confidence: 99%
“…In order to be able to compare our results with the existing literature on joint action (Sebanz et al 2006) and linguistic task switching (Liu et al, 2014), we defined two different time-windows of interest for N2 and P3b components.…”
Section: Eeg Electrode Regions Of Interestmentioning
confidence: 99%